Application of the Certainty Factor Method for Diagnosing Osteoarthritis Using the Python Programming Language - Muntiari, Novita Ranti; Hanif , Kharis Hudaiby (Peneliti Teknologi Teknik Indonesia, 2023)
Osteoarthritis is a disease that causes the joints in the bones to become weaker and less able to function properly. Osteoarthritis can cause pain, stiffness, and even deformity in the joints. The solution to the problem of diagnosing Osteoarthritis is to use a tool, namely a system (expert system) that uses computer technology to make decisions more easily, effectively and efficiently. This study uses the Certainty Factor method in diagnosing osteoarthritis and uses 8 symptoms, namely, pain in the joints, joints feel stiff, clicks or cracks appear when the joints are bent or moved, joints lose their flexibility properties, joints feel softer when pressure is applied, spurs appear bones around the joints, namely hard and sharp bony protrusions, swelling around the joints, and muscles around the joints. The conclusions from the calculations and program implementation, the application of the certainty factor in diagnosing osteoarthritis with existing test data, results in 95.38% that the patient has severe symptoms of osteoarthritis, so he must be taken to an orthopedic specialist.